Genetic diversity and fine-scale spatial genetic structure of the near-threatened Pinus gerardiana in Gardiz, Afghanistan - Moosavi, Sayed Jalal; Budde, Katharina Birgit; Mueller, Markus; Gailing, Oliver (Plant ecology and evolution, 2022)
Background and aims – Chilgoza pine ( Pinus gerardiana) is a near-threatened tree species from the north-western Himalayas. This species is the economically most important pine in Afghanistan because of its edible nuts; however, its distribution range is disjunct and restricted to a few isolated regions. The IUCN lists Chilgoza as a near threatened species because of overexploitation of its nuts and a declining population trend. This research is the first in-depth analysis of the genetic variability and structure of Chilgoza in Afghanistan using microsatellite markers. Material and methods –We tested cross-amplification of 44 SSR markers developed for pine species. Eight polymorphic EST-SSRs were genotyped in a natural Chilgoza population in Gardiz, Afghanistan. To evaluate the genetic diversity, fine-scale spatial genetic structure (SGS), signatures of bottleneck events, and the effective population size, 191 trees were sampled and genotyped. Based on the diameter at breast height, individuals were classified as young or old trees. Key results – Genetic variation in the whole population was moderate. For individual markers, H e ranged from 0.130 to 0.515 (mean = 0.338) and H o from 0.118 to 0.542 (mean = 0.328). The expected heterozygosity in young trees was slightly lower than in old trees. The SGS was stronger for young trees ( Sp = 0.0100) than for old trees ( Sp = 0.0029). Heterozygosity excess analysis detected no recent population size reduction, but the M ratio revealed an ancient and prolonged bottleneck in the Chilgoza population. Conclusion – Identification of suitable EST-SSRs for future studies of natural Chilgoza populations provides important tools for the conservation of the species. Despite the moderate genetic variation in Gardiz, scarcity of natural regeneration is likely to reduce the genetic variation and adaptability in future generations. Our results indicated a slight decrease in genetic diversity and stronger SGS in young trees calling for conservation measures fostering natural regeneration.